(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Computed tomography (CT) continues to evolve, with significant advancements in recent years. This research explores two critical techniques: dual-energy CT (DECT) and low-dose CT. • Dual-Energy Computed Tomography (DECT): - DECT utilizes two distinct X-ray energy levels for material differentiation. - Applications include virtual monoenergetic images, material decomposition, and iodine concentration maps. - Recent research findings demonstrate its value in various clinical scenarios. • Low-Dose CT: - LDCT reduces radiation exposure while maintaining diagnostic quality. - Crucial for lung cancer screening, LDCT detects early-stage nodules. - The National Lung Screening Trial (NLST) supports its efficacy in reducing lung cancer-related deaths.